Pendampingan Pelestarian Budaya sebagai Objek Wisata melalui Festival Kampung - Wenny Ira Reverawaty; Muhammad Yusuf; Ardiyansyah Ardiyansyah (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2019)
The tourism potential in Senaung village has a character because there are history and culture as a representation of the past life of the Jambi people. However, the tourism potential has not well managed and has not developed as a source of income for the community. Through the community engagement program, the team formulated solutions in the form of cultural preservation by identifying tourist objects that have not detected, recording and documenting historical objects, old buildings, and objects, and set tourist objects for performances at village festivals. Mentoring conducted through the provisioning, training, and mentoring programs. Then, the promotion of attractions is spread through social media. The results of the mentoring activities show that there is an increase in awareness, knowledge, concern, and cultural preservation skills that have an impact on the new sources of community income. Cultural preservation through village festival activities in Senaung village is useful for inheriting culture, traditions, and diverse historical heritage.